Lower prevalence of proliferative diabetic retinopathy in elderly onset patients with diabetes. (March 2017) - Zhang, Siqin; Wang, Jianglan; Song, Chenxi; Zhu, Leilei; Yu, Yerong
Highlights: Elderly onset diabetes had low PDR prevalence. Lower IGF-1 levels in older patients may contribute to low PDR prevalence. Less stringent glycemic control in older diabetes may not increase the PDR prevalence. Abstract: Aims: To assess diabetic retinopathy (DR) prevalence between elderly onset and younger onset diabetes with similar diabetes duration and evaluate the association between DR prevalence and serum insulin-like growth factor 1 (IGF-1) levels. Methods: A total of 1787 patients with diabetes were enrolled between January 2010 and November 2015. Fundoscopy examination was performed. Patients were divided into three groups by age of diagnosis (<45, 45–64, and ⩾65 years) for the analysis of the prevalence of DR. Among them, 150 patients underwent serum IGF-1 measurement. The serum IGF-1 level was compared between patients <65 years and ⩾65 years. Results: Among 1787 patients, 779 (43.6%) had DR, in which proliferative DR (PDR) 229 (12.8%) patients. For similar diabetes duration, DR prevalence was lower in elderly onset patients. Patients ⩾65 years at diagnosis had significantly lowest PDR prevalence of the three groups for similar diabetes duration. IGF-1 levels were lower in patients ⩾65 years than in patients <65 years (104.89 ± 49.91 ng/mL vs. 141.73 ± 62.04 ng/mL, P < 0.001). Conclusions: Elderly onset patients with diabetes have lower prevalence of PDR than those younger onset patients for similar diabetes duration, which may relate with lower serum IGF-1 levels in older patients. Thus, less stringent glycemic control in older onset patients with diabetes may not increase the prevalence of PDR.